Cationic Porphyrin Induced a Telomeric DNA to G-Quadruplex Form in Water. (21st January 2008) - Murashima, Takashi; Sakiyama, Daichi; Miyoshi, Daisuke; Kuriyama, Masanori; Yamada, Takashi; Miyazawa, Toshifumi; Sugimoto, Naoki
Abstract : The formation of the DNA G-quadruplex is induced by the addition of a novel porphyrin carrying four cationic tethers. Circular dichroism spectroscopy reveals that the porphyrin binds to Tetrahymena telomeric repeat to form G-quadruplex under stabilizing-cation-deficient and no buffer conditions.